The OMERACT Ultrasound Group: A Report from the OMERACT 2016 Meeting and Perspectives - Terslev, Lene; Iagnocco, Annamaria; Bruyn, George A. W.; Naredo, Esperanza; Vojinovic, Jelena; Collado, Paz; Damjanov, Nemanja; Filer, Andrew; Filippou, Georgios; Finzel, Stephanie; Gandjbakhch, Frederique; Ikeda, Kei; et al. (Journal of Rheumatology, 2017)
To provide an update from the Outcome Measures in Rheumatology (OMERACT) Ultrasound Working Group on the progress for defining ultrasound (US) minimal disease activity threshold at joint level in rheumatoid arthritis (RA) and for standardization of US application in juvenile idiopathic arthritis (JIA).For minimal disease activity, healthy controls (HC) and patients with early arthritis (EA) who were naive to disease-modifying antirheumatic drugs were recruited from 2 centers. US was performed of the hands and feet, and scored semiquantitatively (0-3) for synovial hypertrophy (SH) and power Doppler (PD). Synovial effusion (SE) was scored a binary variable. For JIA, a Delphi approach and subsequent validation in static images and patient-based exercises were used to developed preliminary definitions for synovitis and a scoring system.For minimal disease activity, 7% HC had at least 1 joint abnormality versus 30% in the EA group. In HC, the findings of SH and PD were predominantly grade 1 whereas all grades were seen in the EA cohort, but SE was rare. In JIA, synovitis can be diagnosed based on B-mode findings alone because of the presence of physiological vascularization. A semiquantitative scoring system (0-3) for synovitis for both B-mode and Doppler were developed in which the cutoff between Doppler grade 2 and grade 3 was 30%.The first step has been taken to define the threshold for minimal disease activity in RA by US and to define and develop a scoring system for synovitis in JIA. Further steps are planned for the continuous validation of US in these areas.
EVALuna2:13425